Neck swelling and airway narrowing as an initial manifestation of giant cell arteritis. Issue 3 (15th March 2021) - Lim, Zhen Sheng; Sharp, Colin
Abstract : Giant cell arteritis can result in a wide range of symptoms due to the extensive distribution of the external carotid artery. Face and neck swelling and trismus are under-recognised features of giant cell arteritis and can present as the initial symptom prior to the development of classical temporal tenderness and jaw claudication. The lack of awareness of the less common symptoms may result in a late diagnosis of giant cell arteritis, leading to irreversible vision loss. In this paper, we present a case of neck swelling and airway narrowing as the initial manifestation of giant cell arteritis.